Being Mortal : Ageing, illness, medicine, and what matters in the end - Gawande, Atul (London : Profile Books, 2014)
Gawande, a practicing surgeon, addresses his profession's ultimate limitation, arguing that quality of life is the desired goal for patients and families of the terminally ill.
The independent self -- Things fall apart -- Dependence -- Assistance -- A better life -- Letting go -- Hard conversations -- Courage.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
CIP data; item not viewed.
WorldCat record variable field(s) change: 650
Keywords: Mortality; Death -- Psychological aspects; Attitude to Death; Mortality; mortality; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Electronic books; Electronic books